PENGARUH PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN DENGAN ANALISA DATA PANEL PADA MULTI-BISNIS DI BURSA EFEK INDONESIA PERIODE 2007-2017 - Jan Horas Veryady Purba (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2020)
The issue of dividends is very important to show the prospects for the company's growth in the future, and also important in the company's capital structure. Dividend policy can be influenced by profitability and other variables. In this study, profitability is chosen due to its role as main indicator that shows the company's capacity to pay dividends. This study aims to analyze the effect of profitability on dividend policy. The study population is a company listed on the Indonesia Stock Exchange. Purposively selected eight companies that have a good liquidity category. Data for each company is taken from 2007 to 2017. With this data structure, the analysis used is panel data regression analysis. Panel data analysis models include the Common Effect Model (CEM) Fixed Effect Model (FEM) and Random Effect Model (REM). The best model was tested with the Chow test and Hausman Test and obtained The Fixed Effect Model. Dividend policy is measured by the variable dividend payout ratio. The findings in this study conclude that the dividend policy (Dividend Payout Ratio) is influenced by ROE, EPS and NPM, where these independent variables have a positive and significant influence on DPR.